The Nature and Functions of Research Design in Arabic Language Studies: A Comparative Analysis of Arab, Western, and Indonesian Perspectives - Khilya Kholilah; Asita Sabilla; Nayla Tiara Latifa Al Haq; M Abdan Masykur (UIN Sunan Gunung Djati Bandung, 2026)
Selecting an appropriate research design remains a persistent methodological challenge for students and novice researchers, particularly in Arabic language studies. Comparative studies of research design from both Arab and Western perspectives are still limited, while most methodological literature focuses only on technical aspects without addressing the philosophical dimension. This study aims to analyze the nature and function of research design comparatively based on Arab, Western, and Indonesian literature. The study employs a qualitative approach using library research methods. Data were collected from purposively selected methodological literature based on scholarly relevance and authority. The results indicate that: (1) the nature of research design is a logical, systematic, and paradigmatic methodological framework that integrates research problems, objectives, instruments, and analysis into a unified system; (2) its functions include serving as a research guideline, ensuring validity and reliability, bridging theory and practice, and enhancing efficiency; (3) a notable difference exists between Arab literature, which tends to emphasize philosophical-epistemological dimensions, and Western literature, which focuses more on procedural-technical aspects. This study contributes a conceptual mapping of research design relevant to Arabic language researchers in Indonesia.